Effects of Furazolidone on the Infection of Vibrio cholerae by Bacteriophage φ149 - Chatterjee, S. N. (1973)
Furazolidone in concentrations which had little effect on the growth of host organisms greatly reduced the yield of phage φ149 from the host Vibrio cholerae OGAWA 154. This phage was resistant to the in vitro action of the drug. The phage yield of infected bacteria depended significantly on the time of addition or withdrawal of the drug. The average burst size of the drug-treated and infected bacteria decreased exponentially with increase in drug concentration. The latent period of phage multiplication and also the eclipse period did not change significantly from the control values. A concentration of 0.05 μg of furazolidone per ml inhibited DNA synthesis by about 50% in phage-infected cells and only by about 18% in noninfected ones, relative to the respective controls. RNA and protein synthesis were affected by a much smaller degree both in infected and noninfected cells. Quantitative deduction of the length of furazolidone-treated cells from their phage adsorption characteristics and its agreement with previous electron microscopy data indicated that furazolidone did not affect the phage receptors.